CFD-Based Comparative Analysis of Conical Dimple and Conical Protrusion in a Reverse Flow Solar Air Heater - Abioye, Adekunle (Jurnal Internasional Penelitian Teknologi Terapan, 2024)
This study examined the thermohydraulic performance of reverse flow solar air heaters (RFSAH) incorporating conical surface roughness geometries. A 3D computational fluid dynamics (CFD) model, developed using SolidWorks 2022, was employed to simulate heat transfer enhancement. The simulation utilized the average August solar radiation data for Bauchi, Nigeria (567 W/m²). Two conical roughness configurations were investigated, dimples and protrusions. The effects of the Reynolds number, pitch ratio, and height ratio on the heat transfer and fluid flow were analysed. The results revealed that conical protrusions exhibited a higher peak thermohydraulic performance factor (TPF) of 3.899. The optimal conditions for conical protrusions were determined to be Re = 5988.84, P/e = 5.7, and e/D = 0.2127, achieving a TPF of 5.0672, a 1.3-fold increase compared with unoptimized protrusions. These findings showed the potential of using surface geometries to enhance the efficiency of solar thermal systems while maintaining a favourable balance between the performance and pressure drop.